Uplink detection performance regarding bandwidth-efficient broadband transmission in a large-scale MU-MIMO System - Torres, Paulo (2018)
This paper deals with Single Carrier/Frequency Domain Equalization (SC/FDE) for uplink transmission within a Multi-User (MU) Multi-Input Multi-Output (MIMO) system where the number of Base Station (BS) antennas can be much larger than the number of transmitter antennas jointly using the same time/frequency resource at Mobile Terminals (MT). Selected Quadrature Amplitude Modulation (QAM) schemes are assumed for transmission, so that high bandwidth efficiencies are achievable. In this context, we consider either a linear detection or a reduced-complexity, iterative Decision Feedback (DF) detection, evaluate the achievable performances in both cases, and discuss them with the help of selected performance bounds and semi-analytically evaluated error floor levels. From our performance results, we conclude that simple linear detection techniques, designed to avoid the need of complex matrix inversions, can lead to unacceptably high error floor levels. However, by combining the use of such simple linear detectors with the appropriate interference cancellation procedure - within the iterative DF technique -, a close approximation to the Single-Input Multi-Output (SIMO) Matched-Filter Bound (MFB) can be achieved after a few iterations, even for 64-QAM schemes, when the number of BS antennas is five times higher than the number of antennas jointly used at the user terminals.